LITERATURE REVIEW: PENGEMBANGAN STRATEGI PEMASARAN PARIWISATA DALAM MENINGKATKAN NIAT BERKUNJUNG WISATAWAN DI INDONESIA - Rangga Prayogo; Roziana Febrianita (Jurnal Ilmu Administrasi dan Bisnis, 2018)
Tourism is a global industry that can revive a country through the foreign exchange gained to grow the Indonesian economy. The development of tourism in Indonesia is still experiencing many obstacles to develop it both the infrastructure sector and services that have not been maximized. It takes the development of tourism strategies to make tourists come to Indonesia. Strategy development is needed to support government programs in the maritime sector to optimize existing resources. Indonesia is a country with many beautiful islands, one of which is Sabang Island. Sabang Island is a small paradise owned by Indonesia that can be a destination for tourists to visit both local and foreign. With the development of tourism strategies are expected to increase local people's income. The development of a tourism strategy consisting of e-wom, destination image, and travel motivation is very important to attract tourists. From this phenomenon, researchers see the relationship between the two through a literature review and literature approach to see the relationship between the development of tourism strategies and tourist visiting intentions. This paper provides definitions, domains, dimensions and determinants of the development of tourism strategies and the intention to visit tourists on the island of Sabang to become a study article and can be continued for future research.Keyword: Indonesian tourism, tourism strategy development, tourist visiting intension.